Bijective Crossovers

Algebra Level 4

The function f ( x ) = x 3 + 1 4 x 1 4 f(x) = x^3 + \frac {1}{4} x - \frac {1}{4} is a monotonically increasing function, hence it is injective (one-to-one), so its inverse function exists and is well defined. How many points of intersection are there, between the function f ( x ) f(x) and its inverse f 1 ( x ) f^{-1}(x) ?


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

14 solutions

Finding intersections between f ( x ) f(x) and f 1 ( x ) f^{-1}(x) is similar to finding the number of values of x x such that f ( x ) = f 1 ( x ) f(x) = f^{-1}(x) , or f ( f ( x ) ) = x f(f(x)) = x .

Case 1: f ( x ) = x f(x) =x for some x x , then f ( f ( x ) ) = f ( x ) = x f(f(x)) = f(x) = x . This implies x 3 + 1 4 x 1 4 = x x^3+ \frac 14 x -\frac 14 =x , or x 3 3 4 x 1 4 = 0 x^3- \frac 34 x - \frac 14 = 0 , which can also be written as 1 4 ( x 1 ) ( 2 x + 1 ) 2 = 0 \frac 14 (x-1)(2x+1)^2 = 0 . This equation has two real solutions, namely 1 2 , 1 -\frac {1} {2}, 1 .

Case 2: Now, let for some x x , f ( x ) = k x f(x) = k \neq x , then, as f f is monotonically increasing, if k > x k>x , then f ( k ) f ( x ) > x f(k) \geq f(x) > x , or f ( f ( x ) ) > x f(f(x)) > x , again if k < x k<x , then f ( k ) f ( x ) < x f(k) \leq f(x) < x , or f ( f ( x ) ) < x f(f(x)) < x . So the condition f ( x ) = x f(x) = x is necessary and sufficient for f ( f ( x ) ) = x f(f(x)) = x being true.

Thus, there are only 2 points of intersections.

This is the only correct solution. All others were marked wrong.

Though f ( x ) f(x) and f 1 ( x ) f^{-1}(x) are symmetric about the line y = x y=x , it is not true that f ( x ) f(x) and f 1 ( x ) f^{-1} (x) only intersect on the line y = x y=x . For example, consider the function a ( x ) = 1 x a(x) = \frac {1}{x} . The inverse of this function is the function itself, and it has a lot of points of intersection that do not lie on y = x y=x . Mohsinur correctly classifies the points of intersection as solutions to x = f ( f ( x ) ) x = f(f(x)) .

If however, we know further that the function is monotonically increasing, then it is true that f ( x ) f(x) and f 1 ( x ) f^{-1} (x) only intersect on the line y = x y=x , as Mohsinur shown in Case 2.

Calvin Lin Staff - 7 years ago
Billy Floyd
May 20, 2014

Due to the symmetry of f ( x ) f(x) and f 1 ( x ) f^{-1}(x) about the line y = x y=x , we need only to see where the curves f ( x ) f(x) and y = x y=x intersect. Put differently, we must find the roots of g ( x ) = x 3 3 4 x 1 4 g(x)=x^3-\frac{3}{4}x-\frac{1}{4} .

Immediately we see that x = 1 x=1 is a solution to g ( x ) g(x) . Polynomial long division leaves us with g ( x ) = ( x 1 ) ( x 2 + x + 1 4 ) g(x)=(x-1)(x^2+x+\frac{1}{4}) . Note that the discriminant of ( x 2 + x + 1 4 ) (x^2+x+\frac{1}{4}) , 1 ( 4 ) ( 1 ) ( 1 4 ) 1-(4)(1)(\frac{1}{4}) , equals zero so ( x 2 + x + 1 4 ) (x^2+x+\frac{1}{4}) has only one solution. Using the quadratic formula, we obtain x = 1 2 x=-\frac{1}{2} .

We can now completely factor g ( x ) = x 3 3 4 x 1 4 g(x)=x^3-\frac{3}{4}x-\frac{1}{4} into g ( x ) = ( x 1 ) ( x + 1 2 ) 2 g(x)=(x-1)(x+\frac{1}{2})^2 . It is very easy to see that g ( x ) g(x) has two roots, and thus f ( x ) f(x) and f 1 ( x ) f^{-1}(x) intersect exactly twice, at ( 1 , 1 ) (1,1) and ( 1 2 , 1 2 ) (-\frac{1}{2},-\frac{1}{2})

What is wrong with the logic in the first paragraph?

Hint: Apply his argument to the function f ( x ) = x f(x) = -x . What is the inverse of this function? What are the points of intersection of this function and its inverse?

Calvin Lin Staff - 7 years ago
Abhishek Kumar
May 20, 2014

firstly draw the graph of f(x) then draw the graph of f inverse x by taking symmetry along the line x=y then using both the graphs there will be two points of intesection

Calvin Lin Staff
May 13, 2014

Finding intersections between f ( x ) f(x) and f 1 ( x ) f^{-1}(x) is similar to finding the number of values of x x such that f ( x ) = f 1 ( x ) f(x) = f^{-1}(x) , or f ( f ( x ) ) = x f(f(x)) = x .

Case 1: f ( x ) = x f(x) =x for some x x , then f ( f ( x ) ) = f ( x ) = x f(f(x)) = f(x) = x . This implies x 3 + 1 4 x 1 4 = x x^3+ \frac 14 x -\frac 14 =x , or x 3 3 4 x 1 4 = 0 x^3- \frac 34 x - \frac 14 = 0 , which can also be written as 1 4 ( x 1 ) ( 2 x + 1 ) 2 = 0 \frac 14 (x-1)(2x+1)^2 = 0 . This equation has two real solutions, namely 1 2 , 1 -\frac {1} {2}, 1 .

Case 2: Now, let for some x x , f ( x ) = k x f(x) = k \neq x , then, as f f is monotonically increasing, if k > x k>x , then f ( k ) f ( x ) > x f(k) \geq f(x) > x , or f ( f ( x ) ) > x f(f(x)) > x , again if k < x k<x , then f ( k ) f ( x ) < x f(k) \leq f(x) < x , or f ( f ( x ) ) < x f(f(x)) < x . So the condition f ( x ) = x f(x) = x is necessary and sufficient for f ( f ( x ) ) = x f(f(x)) = x being true.

Thus, there are only 2 points of intersections.

Note: It is not true that f ( x ) f(x) and f 1 ( x ) f^{-1} (x) only intersect on the line y = x y = x . For example, the inverse of f ( x ) = 1 x f(x) = \frac {1}{x} is the function itself. If however we know that the function is monotonically increasing, then f ( x ) f(x) and f 1 ( x ) f^{-1} (x) only intersect on the line y = x y = x .

Akbarali Surani
May 20, 2014

If f is a function such that f:A->B then its inverse f-1(x) is such that f-1(x):B->A For point of intersection, f(x)=f-1(x) so x^3+(1/4)x-(1/4)=x =>4x^3-3x-1=0 =>(x-1)(2x+1)^2=0 =>x=1,x=(-1/2). Therefore two points of intersection.

Oliver Prior
May 20, 2014

I began by sketching what the cubic would have to look like to be injective then considered what the inverse function is (a reflection in y = x) this then implied that the roots of f^-1(x) = f(x) were where f(x) = x. By equating, x = x^3 + 1/4 x - 1/4 hence x^3 - 3/4 x - 1/4 = 0 => (x-1)(x+ 1/2)^2 = 0 hence there are two unique points of intersection.

용철 고
May 20, 2014

Follow Key technique and then f(x)-x=(x^3+1/4x-1/4)-x=x^3-3/4x-1/4=0 Multiply it by 4 and factorize for x then you'll get (x-1)(2x-1)^2=0 (x-1)=0 has one solution x=1 and (2x-1)^2=0 has one solution x=1/2 Hence function f intersect it's inverse function at two points

Prem Singh
May 20, 2014

If f is invertible (and it is invertible, you found the inverse), then the graph of the inverse function is reflection about the line y=x If they intersect, they will need to intersect on the line y=x So, we can solve the equation

x = f(x)

Reevu Ghosh
May 20, 2014

The given function is one-one. So the oversee function exists. now if f(a)=b then f-1(b)=a. So the f(x)&f-1(x) are symmetric about the line y=x.so f(x) intersects f-1(x) at the line y=x i.e.the solutions of f(x)&f-1(x) is same to that of f(x)=x. The solutions are 1,1,•5.so the function intersect its inverse function at two distinct points 1&•5.

Note that the points of intersection of y = f ( x ) y=f(x) and y = f 1 ( x ) y=f^{-1}(x) lie on the line y = x y=x , because every point of y = f 1 ( x ) y=f^{-1}(x) is the reflection of y = f ( x ) y=f(x) across y = x y=x . Thus, we are left to finding the number of points of intersection of y = f ( x ) = x 3 + 1 4 x 1 4 y=f(x)=x^3+\frac{1}{4}x-\frac{1}{4} and y = x y=x . Substituting, we get the cubic equation x 3 3 4 x 1 4 = ( x 1 ) ( x + 1 2 ) 2 = 0 x^3-\frac{3}{4}x-\frac{1}{4}=(x-1)\left(x+\frac{1}{2}\right)^2=0 . Since there are 2 2 real roots, there are 2 2 points of intersection.

Tim Ye
May 20, 2014

(might not be right)

You know what a hyperbola looks like.

Then, if you picture it in your head sideways, you can see that there can only be two intersections.

The final answer would have to be two no matter what.

Leah Tom
May 20, 2014

X^3 + 1/4 x-1/4=x The above step is justified because f(x) and f^-1(x) are symmetrical about line y=x. Hence at the intersection points between f^-1(x) and f(x), y=x also intersects the other 2 graphs. Subsequently, we can solve the cubic equation.

X^3-3/4X-1/4=0 4x^3- 3X -1 = 0 By substituting in 1, we can see that x-1 is a factor. (X-1)(4X^2+4X+1)=0 (X-1)(2x+1)^2=0

Simon Lee
May 20, 2014

if f(x) and inverse function meet, then the points must be on the function y=x because f(x) is a monotonically increasing function. this means there will be no points f(x) and inverse function meet which are not on the function y=x. so, solve the equation f(x)=x, then find the number of value. then that's answer :)

they are symmetric by y=x. equation x^3+x/4-1/4=x has 2 roots

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...